An analysis of supply chain management research by topic. Issue 2 (30th April 2018) - Swanson, David; Goel, Lakshmi; Francisco, Kristoffer; Stock, James
Abstract : Purpose: This paper aims to review logistics and supply chain management topics where theories have been applied to better understand the supply chain management (SCM) discipline identity. The purpose is threefold: to identify research topics in logistics and supply chain management where one or more theories have been examined; provide commentary on the theories that have been applied to the various logistics and SCM research topics; and to provide reference material and direction for future research. Design/methodology/approach: This structured literature review (SLR) examines research papers in logistics and SCM from 1991 to 2015 published in eight leading academic journals. Papers in the data set are grouped by topic and further analyzed in terms of research method, purpose, year and journal. Findings: This research categorizes papers by the topics that were studied to understand important insights about how these topics have been examined by researchers. Within each topic area, theories that researchers have used to investigate the topics are identified. This method exposes insights such as: how topics have evolved over time, which topics have lost prominence, which topics may be particularly promising for future research and how topics are treated in the literature. Originality/value: Despite multiple calls for clarification regarding how theory has been used in logistics and SCM, the logistics and SCM disciplines continue to grow without adequate research on how theory has been used to examine SCM topics. This SLR therefore provides a broad compilation of logistics and SCM research that uses named theories and that is organized by SCM topic to better understand the SCM discipline.